2004
DOI: 10.1002/mame.200300290
|View full text |Cite
|
Sign up to set email alerts
|

The Solid State Postcondensation of PET, 2

Abstract: Summary: A process for the solid state polycondensation of PET is proposed. It is shown that by correctly choosing the prepolymerisation conditions it is possible to crystallise the product and to directly polymerise it in a dispersed phase. This process is significantly faster than the “standard” PET processes, and allows one to obtain high molecular weights directly from a prepolymer without the need to use an intermediate solution polymerisation step.Reactor set‐up for precursor preparation and dispersed ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 3 publications
0
27
0
1
Order By: Relevance
“…The solid state polycondensation of PET was recently presented in an excellent and detailed review by the group of McKenna. [181] The main reactions involved in the SSP of PET include the ones shown in Scheme 4. During SSP due to the low reaction temperature, chain mobility is relatively low compared to corresponding melt polymerization process.…”
Section: Solid State Polycondensation Of Polyestersmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid state polycondensation of PET was recently presented in an excellent and detailed review by the group of McKenna. [181] The main reactions involved in the SSP of PET include the ones shown in Scheme 4. During SSP due to the low reaction temperature, chain mobility is relatively low compared to corresponding melt polymerization process.…”
Section: Solid State Polycondensation Of Polyestersmentioning
confidence: 99%
“…Thus, they assumed that the mobility of the end-groups and consequently the value of the rate coefficient depended on the free volume of the polymer that decreases with reaction time. According to Gantillon et al, [181] if it is considered that PET is a semi-crystalline material, then it is not realistic to consider that the entire macromolecule could diffuse through the matrix on a time scale proportionate with that of the polycondensation. Also not only the local viscosity on the amorphous phase is very high, but a large fraction of macromolecules remain trapped in crystalline occlusions in the polymer matrix.…”
Section: Solid State Polycondensation Of Polyestersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the polyester industry, it is common practice to calculate M n -with the help of simple linear empirical relationships between molar mass and reduced viscosity. As an example, very helpful equations have been proposed by Gantillon et al [36] for poly(ethylene terephthalate).…”
Section: Correlation Between Reduced Viscosity and Molar Massmentioning
confidence: 99%
“…In Part 2 of this series, [1] it was demonstrated that it is possible to produce high molecular weight PET (a weightaverage molecular weight (M w ) over 50 000) in a dispersed phase, solid state postcondensation (SSP) process. The process proposed consisted of four steps: formulation of the precursor, prepolymerisation, rapid cooling and crystallisation of the prepolymer and SSP.…”
Section: Introductionmentioning
confidence: 99%